DEVELOPMENT OF INSTITUTIONAL INSTITUTIONS IN ANDALUS IN THE ABAD TO 10M TO 13M - Dr. Salmah Binti Omar; Dr. Syahrul Faizaz Binti Abdullah (Journal of Islamic, Social, Economics and Development, 2017)
The majesty of Andalus or now known as Spain lies in its superior position in science. Andalus is not only a center of Islamic sciences but also the field of science and philosophy. Here is the birth of famous Islamic scholars such as Ibn Rusyd, Ibn Hayyan, Ibn Baythar, Ayesah, Ziryab. One of the factors that led to its excellence as a center of science for the existence of educational institutions of initiative from the ruling class, the clerics of scholars to the common people. Hence this article aims to discuss the births and developments of scientific institutions in Andalus by focusing in the 10M to 13M centuries by using a text analysis method. The analysis of the study found that educational institutions in Andalus can be categorized with informal institutions and formal institutions. Informal institutions consist of private homes, mosques, caliphs, viziers or governors and libraries. Formal education can consist of schools and universities. Each institution is both formal and informal as it has contributed to the cultivation of knowledge and scholarship in all walks of life, raising Andalus as a Center of Knowledge which focuses on either the East and the West.